Real-time observation of the spin Hall effect of light using metasurface-enabled single-shot weak measurements - Jinkyeong Lee; Jaekyung Kim; Sangmin Shim; Younghwan Yang; Jeonghoon Choi; Junsuk Rho; Dasol Lee; Minkyung Kim (Nature Communications)
Abstract The spin Hall effect of light (SHEL), the transverse splitting of light into two circularly polarized components via refraction or reflection, offers high-precision, nondestructive inspection of unknown interfaces when combined with a signal amplification technique called weak measurement. However, its application in detecting dynamics is limited due to its multistep process. Here, we condense the procedure into a single step, enabling calibration-free, single-shot measurement of the SHEL by replacing one component of the conventional setup with a polarization beamsplitting metasurface. Our approach allows for instantaneous evaluation of the SHEL, even with fluctuations in the original beam position. As proof of concept, we apply metasurface-assisted weak measurements to both static and dynamic scenarios, where the experimental results obtained from a single captured image demonstrate nice agreement with theory. This real-time observation of the SHEL highlights its potential for high-precision monitoring of dynamic processes such as biomedical sensing and chemical analysis.